Efficacy and safety of vesicular monoamine transporter 2 inhibitors for Huntington’s disease chorea based on network meta-analysis - Huang, Jing; Chen, Fei-Fei; Wen, Si-Yuan; Tao, Pan; Meng, Chi; Chen, Wei; Zhou, Chang-Qing (Frontiers in Pharmacology, 2025)
ObjectiveA Bayesian network meta-analysis was conducted to evaluate the efficacy, tolerability, and safety of vesicular monoamine transporter 2 (VMAT2) inhibitors in Huntington’s disease chorea.MethodsThe MEDLINE, Embase, and Cochrane Central Register of Controlled Trials were searched from January 1970 to January 2025 for eligible randomized controlled trials. Three VMAT2 inhibitors, including tetrabenazine, deutetrabenazine and valbenazine were investigated. The network meta-analysis was conducted based on a Bayesian framework using a fixed-effects model. As there were no closed loops in the network plot, comparisons of these interventions were directly formed by a consistency model.ResultsThree randomized controlled trials (n = 299 patients) were included in the analysis. The surface under the cumulative ranking curve indicated that tetrabenazine was associated with the greatest improvement in the Unified Huntington’s Disease Rating Scale Total Maximal Chorea score (0.878), followed by valbenazine (0.700) and deutetrabenazine (0.422). Meanwhile, in the Unified Huntington’s Disease Rating Scale Total Motor score, valbenazine ranked highest, with a score of 0.781. Deutetrabenazine ranked highest in terms of overall withdrawals (0.800) and adverse events (AEs) (0.688), while valbenazine ranked first in withdrawals due to AEs (0.735), serious adverse events (0.807), as well as in reducing both suicide (0.683) and suicidal ideation (0.748).ConclusionThis study suggests that three VMAT2 inhibitors are effective in ameliorating chorea symptoms in patients with Huntington’s disease. Tetrabenazine is the most effective in controlling chorea, whereas valbenazine may be the optimal choice for patients with comorbid psychiatric symptoms.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251012431, identifier CRD420251012431.